EFEK APLIKASI Trichoderma sp. DAN BOKASHI TERHADAP PERTUMBUHAN BIBIT KAKAO YANG DITANAM PADA TANAH TERINFEKSI Phytophthora palmivora. - Kalay, A. Marthin; Latupapua, Andreas I; Talahatu, Hellen (Jurnal Agroekoteknologi, 2015)
Phytophthora sp. is one species of fungus that attacks the seeds of the cocoa plant. Control may use biological agents and Bokashi. This study aimed to determine the effect of Trichoderma sp. and Bokashi on the growth of plants and pathogens Phytophthora sp on cocoa plant in nurseries. The treatment was Trichoderma sp at a doses that was 0 gram, 25 grams, 50 grams and 75 grams, and Bokashi at a doses of 0 gram, 25 grams, 37.5 grams and 50 grams. The study was designed using a completely randomized design with three replications. The results showed that administration of Trichoderma sp. and Bokashi jointly improve the interaction effects canopy height, canopy fresh weight and shoot dry weight, and suppress the intensity of the disease. A dose of 75 grams of Trichoderma sp + 50 grams Bokashi is best dose increase canopy height, canopy fresh weight and shoot dry weight. A dose of 50 grams Bokashi without giving Trichoderma sp. can reduce the disease intensity to 14.95%, and a dose of 25 grams of Trichoderma sp, with or without the provision of Bokashi can reduce the disease intensity to 0%.